On the Left Properness of the Model Category of Permutative Categories - Amit Sharma (Axioms, 2023)
In this paper, we introduce a notion of free cofibrations of permutative categories. We show that each cofibration of permutative categories is a retract of a free cofibration. The main goal of this paper is to show that the natural model category of permutative categories is a left proper model category.